Strengthening teacher pedagogical literacy after the Covid-19 pandemic in vocational secondary education in Banten Province - Sintha Wahjusaputri; Wati Sukmawati; Tashia Indah Nastiti; Via Noorlatipah (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2022)
The purpose of this study is to improve the pedagogic competence of teachers in implementing literacy in learning through lesson study, namely: socialization, training, self-evaluation, reflective pedagogical paradigm, exploration, simulation, documentation, group discussion, mapping, and practice at SMK Negeri 3 Tangerang Selatan, Banten Province, Indonesia. This type of action research consists of two cycles, each carried out in four meetings. The research procedure includes (1) planning, (2) implementing actions, (3) observing, and (4) reflection. The subjects in the study were productive teachers and normative teachers at SMK Negeri 3 Tangerang Selatan, opening 15 people. The results showed that the teacher's pedagogic competence in implementing literacy in pre-action learning was 37%, the first cycle increased by 83%, and the second increased significantly by 100%. Classically the percentage has increased by 63%. Based on these results, lesson study can improve the pedagogic competence of teachers in implementing literacy in learning at SMK Negeri 3 Tangerang Selatan, Banten Province, Indonesia.